STUDDING OF CHANGES DYNAMICS OF OCCLUSION CONTACTS IN PATIENTS TREATED BY PARTIAL REMOVABLE DENTURES - Штурмак, В. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
This article shows the dynamics of clinical research of the removable dentures produced by various methods. In view of this 124 patients having partial dentition defects complicated by chronic periodontitis of I-II degree of complexity where treated by different types of partial removable dentures and further supervised. While analyzing the occlusion by T-scan III it was found out that in the process of treating the patients having periodontitis of II degree of complexity by partially removable dentures produced by the improved method resulting in usage of Mucopren soft the rapidity of the disease was reduced due to the less negative influence of the mentioned above dentures on the periodontal tissue.